Broncalt®, class II medical device, in patients with acute upper airways disease: a survey in clinical practice - Cupido, Gian Franco; Gelardi, Matteo; La Mantia, Ignazio; Aragona, Salvo Emanuele; Vicini, Claudio; Ciprandi, Giorgio; otorhinolaryngological disorders, Italian Study Group on inflammatory (Acta Biomedica Atenei Parmensis, 2019)
Inflammation is a common pathogenic mechanism involved in many otorhinolaryngological (ORL) disorders. Broncalt® is a class II Medical Device containing: thermal water (Medesano, PR, Italy), hyaluronic acid, and grapefruit seed extract. It has been reported that it exerted a safe and effective anti-inflammatory, washing, and antimicrobial activity by virtue of these components. Therefore, the aim of the current survey, conducted in clinical practice of 84 Italian ORL centers, was to evaluate its safety and efficacy in the treatment of patients with acute upper airways disease. The 3,533 (1,797 males, mean age 43.5 years) patients were evaluated at baseline (T0) and after a 2-week treatment (T1) with or without Broncalt®. Signs and symptoms severity were measured by visual analogue scale. Broncalt® significantly and safely diminished the clinical features in all sub-groups (p